Formulasi dan uji aktivitas repellent lilin aromaterapi dari minyak atsiri serai wangi (Cymbopogon Nardus L.) dengan cengkeh (Syzygium Aromaticum L.) - Ginting , Indra; Rudang , Singgar Ni; Andry, Muhammad (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2024)
Background: Aromatherapy candles are an alternative to inhalation therapy applications, namely the inhalation of aroma vapors produced from essential oils. Fragrant Lemongrass (Cymbopogon nardus L.) and Clove (Syzygium aromaticum L.) contain essential oil compounds that have the potential as natural pesticides. This study aims to formulate aromatherapy candles from essential oils of citronella and clove flowers as mosquito repellents with various concentrations, namely negative control, F1:1%:3%, F2: 2%:2%, and F3: 3%:1 %. The research was done experimentally by making preparations of aromatherapy candles, with preparation evaluation tests including organoleptic tests, air bubble tests, burn time tests, and melting point tests. The candle quality test includes a scent preference test, a candle effectiveness test against mosquitoes, and a therapeutic test on sleep quality using the Mi Band 5 Smartwatch. The results of the preparation evaluation test met the requirements. The most preferred scent was F2 (2%:2%). The effectiveness of wax as a repellent was very optimal in killing mosquitoes, with the best value affecting mosquito mortality shown by F3 treatment (3%:1%). The effectiveness of candles as a therapy for sleep quality showed that there was a change in the quality of sleep that was getting better, with the best value affecting sleep quality shown by the F2 treatment (2%:2%). The conclusion from the researchers of the study is that aromatherapy candle formulations from citronella and cloves can be used as mosquito repellents and also improve sleep quality.